A new methodology for complex societal problems - Dorien J. DeTombe (European Regional Science Association (ERSA), 1998)
Questions on the theme which developments will be in Europe the next ten, thirty to fifty years can be considered as complex societal problems. These problems need an integral approach based on analysis of the temporary situation, with a reflection of the past and focusing on new developments, trends, political values and ideas. Analysing the situation in Europe should be done in accordance to a micro analysis of the states of Europe and a macro analyses of the world. Several issues like finance, economy, infrastructure, internet, environment, employment, knowledge, education, health care, technical developments etc. should be integrated with each other and should be analysed in relation to the legal and political ideas. Many actors with different power and emotions are involved. Analysing as well as predicting future developments should be done with several groups of people. A new methodology is developed that handles these kind of questions. The method support the analysis of the past, the temporary situation and the future, integrating the many different aspects. This new methodology, the method Compram (DeTombe, 1994), is based on the idea that handling complex societal problems is based on knowledge, power and emotion. The method handles these problems with a six step approach starting with analysing the situation with neutral experts from different fields, then analysing the same situation with the different actors, then together based on several scenario's trying to make a picture of future developments. In the paper the method will be described in relation to the questions of future development of Europe.
Keywords: 330